Successful pancreatic pseudocyst drainage using lumen-apposing metal stent for preventing re-rupture of splenic artery pseudoaneurysm - Takashi Ito; Tsukasa Ikeura; Koh Nakamaru; Masataka Masuda; Shinji Nakayama; Makoto Naganuma (International Journal of Gastrointestinal Intervention)
Splenic pseudoaneurysm rupture is a serious condition that sometimes leads to death. Pseudoaneurysm rupture is often treated with transcatheter arterial embolization (TAE), after which the re-rupture rate is 18%-37%. A 59-year-old man presented with back pain, and contrast-enhanced computed tomography (CECT) revealed pancreatic tail cancer with multiple liver metastases. After three courses of chemotherapy, CECT revealed good response with shrinkage of the tumors. However, the patient had back pain and CECT revealed pancreatic pseudocyst with pseudoaneurysm rupture. He underwent angiography, wherein the splenic artery pseudoaneurysm was embolized using TAE. Subsequently, pseudocyst drainage was performed using lumen-apposing metal stent (LAMS) to prevent pseudoaneurysm re-rupture. Thereafter, the pseudocyst shrieked with decreased serum levels of C-reactive protein, allowing the patient to re-institute chemotherapy. Pseudocyst drainage using LAMS was safe and effective when the pancreatic pseudoaneurysm had a high-risk rebleeding due to exposure to pancreatic juice.